MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS MELALUI PERMAINAN â€œCHARADESâ€ PADA SISWA KELAS 5 SDN 3 TEMBUKU, BANGLI DI ERA NORMAL BARU - Ni Putu Yeni Yuliantari; Putu Cita Ayu; Putu Nuniek Hutnaleontina; Ni Made Wisni Arie Pramuki; Ni Putu Ayu Kusumawati (UNHI Press, 2021)
The lack of facilities (such as smartphone or internet signal) and parental assistance during the learning process from home made it difficult for subject materials to be conveyed properly, especially in English lessons. This can be decreased the students' interest and ability in that lesson and continued to face-to-face (offline) meetings. If this happens in the beginning stage, then the students will have difficulty in following the next stages. In order to increase the studentsâ€™ interest and motivation in learning English, this community service is held. Through the games